Perhitungan Kebutuhan Air Irigasi Untuk Daerah Irigasi Batang Sikali, Kota Payakumbuh untuk Peningkatan Hasil Pertanian - Sari, Ridha; Asnur, Hanifah; Yunita, Rini; Khatab, Umar; Ronny Junaidy; Riski Marsa, Arif (Jurnal Pustaka Paket, 2026)
The community service activity represents the implementation of the Tri Dharma of Higher Education, especially in knowledge applications in the field of civil engineering focusing in water resources for community empowerment. The activity entitled Calculation of Irrigation Water Requirements for the Batang Sikali Irrigation Area, Payakumbuh City aims to (1) analyze irrigation water requirements in the Batang Sikali Irrigation Area and (2) to enhance the knowledge of the Water User Farmers Association (P3A) regarding irrigation water requirements to support agricultural production increasing. The activity was conducted in the Batang Sikali Irrigation Area, Payakumbuh City. The methods included the collection of precipitation data, climatological data, cropping patterns, and existing irrigation conditions, followed by the calculation of irrigation water requirements. The results show that the highest irrigation water requirement occurred in the second period of April, amounting to 196.334 m³/ha or 2.272 L/s/ha, while the lowest irrigation water requirement occurred in the first period of April, amounting to 35.511 m³/ha or 0.411 L/s/ha. Through this activity, hopefully the water user association members gained a better understanding of irrigation water requirement calculations and efficient irrigation water management, which is expected to support sustainable irrigation management and improve agricultural productivity.